2004
DOI: 10.1023/b:boli.0000043028.97292.70
|View full text |Cite
|
Sign up to set email alerts
|

Noncirrhotic portal hypertension in association with juvenile nephropathic cystinosis: Case presentation and review of the literature

Abstract: We report a case of portal hypertension and oesophageal varices arising in an 18-year-old female renal transplant recipient with juvenile nephropathic cystinosis diagnosed at 6 years of age. The patient had a history of poor compliance with her prescribed cysteamine therapy. Routine examination revealed normal liver function without hepatomegaly but asymptomatic splenomegaly. An abdominal ultrasound suggested mild oesophageal varices, confirmed later on endoscopy. A liver biopsy revealed an abundance of cystin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…Cystine deposition in Kupffer cells is common, and hepatocyte atrophy, regenerative nodules and gastropathy with varices have also been described [122]. Portal hypertension has been reported in the absence of bridging fibrosis [122][123][124]. Some patients have required portocaval shunting, for esophageal varices and gastrointestinal bleeding, or splenectomy for hypersplenism, thrombocytopenia, leucopenia, and anemia [56].…”
Section: Late Disease Complicationsmentioning
confidence: 99%
“…Cystine deposition in Kupffer cells is common, and hepatocyte atrophy, regenerative nodules and gastropathy with varices have also been described [122]. Portal hypertension has been reported in the absence of bridging fibrosis [122][123][124]. Some patients have required portocaval shunting, for esophageal varices and gastrointestinal bleeding, or splenectomy for hypersplenism, thrombocytopenia, leucopenia, and anemia [56].…”
Section: Late Disease Complicationsmentioning
confidence: 99%
“…They suggested that the deposition of collagen by Ito cells activated by the cystine‐laden Kupffer cells led to hepatic fibrosis and eventual portal hypertension. But, in DiDomenico's case report, however, there was portal hypertension without fibrosis or Ito cell hyperplasia 5 …”
Section: Discussionmentioning
confidence: 86%
“…Cases in the literature most frequently describe non‐cirrhotic portal hypertension due to liver accumulation of cystine with nodular regenerative hyperplasia 4 . DiDomenico reported a patient with cystinosis who developed splenomegaly and mild esophageal varices 5 . Liver biopsy revealed an abundance of cystine crystals within the Kupffer cells but with preserved hepatic architecture.…”
Section: Discussionmentioning
confidence: 99%
“…991 Additional cases of noncirrhotic portal hypertension have been ascribed to cystine accumulation in Kupffer cells. 1418,1419 In two patients, long-term infantile nephropathic cystinosis was associated with a form of sclerosing cholangitis, which responded to therapy with UDCA. 1420 Liver biopsy specimens showed severe accumulation of cystine, predominantly localized in Kupffer cells, together with morphological features of sclerosing cholangitis.…”
Section: Congenital Hyperammonaemia Syndromes and Urea Cycle Disordersmentioning
confidence: 99%